Combined modality radiotherapy for high-risk prostate cancer. Analysis of treatment-Related complications - K. S. Makarova; Yu. V. Gumenetskaya; V. A. Biryukov; A. A. Obukhov; I. A. Strikanova; S. O. Dzhabrailova; O. G. Lepilina; N. B. Borysheva; O. B. Karyakin; S. A. Ivanov; A. D. Kaprin (Сибирский онкологический журнал)
Purpose: to analyze toxicity of combined modality radiotherapy in high-risk prostate cancer patients.Material and methods. Short-term outcomes after combined modality radiotherapy were analyzed in 88 prostate cancer patients treated at clinic of the a.F. tsyb medical Radiological Research center between april 2016 and February 2018. the median follow-up time was 13 months (range, 3–23 months). the mean age of the patients was 64.8 years (range, 49–80 years). an initial psawas in the range of 3.5–114 ng/ml (mean 16.7 ng/ml). all patients were considered high-risk according to the d’amico classification. the patients were divided into two groups according to the sequence of combined modality radiotherapy. in group 1, the patients (n=45) received conformal EBRtto a total dose of 44–46 gy, and 2–3 weeks later, they underwent high–dose rate 192ir- brachytherapy (one single fraction of 15 gy) as a boost to EBRt. in group 2, the patients (n=43) were treated with interstitial brachytherapy followed by EBRtdelivering at total doses of 44–46 gy.Results. All patients eventually completed the combined modality radiotherapy course planned for them. acute, grade 1 genitourinary (gu) toxicities (Rtog/EoRtc) occurred in 29 (32.9 %) patients. acute gastrointestinal (gi) toxicity was grade 1 in 17 (19.3 %) and grade 2 in 2 (2.3 %) patients. late gutoxicity was grade 1 in 6 (6.8 %) and grade 2 in 3 (3.4 %) patients. an urethral stricture developed in 1 (1.1 %) patient. late gitoxicity was grade 1 in 8 (9.1 %) patients and grade 2 in 6 (6.8 %) patients.Conclusion. The preliminary results of this study suggest satisfactory tolerability of combined modality radiotherapy by prostate cancer patients. the level of acute toxicity and complications in critical organs is quite acceptable, which maintains high quality of life for patients and does not exceed the published data.